2014
DOI: 10.5812/iranjradiol.4617
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Bolus Tracking Versus Fixed Time-Delay Technique in Biphasic Multidetector Computed Tomography of the Abdomen

Abstract: BackgroundBolus tracking can individualize time delay for the start of scans in spiral computed tomography (CT).ObjectivesWe compared automatic bolus tracking method with fixed time-delay technique in biphasic contrast enhancement during multidetector CT of abdomen.Patients and MethodsAdult patients referred for spiral CT of the abdomen were randomized into two groups; in group 1, the arterial and portal phases of spiral scans were started 25 s and 55 s after the start of contrast material administration; in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…To maximize contrast enhancement of the target organ for each phase, contrast-enhanced CT techniques such as fixed scan delay, test bolus, and bolus tracking, which provide information for CT scan timing, have been described for multi-phase CT imaging in humans [1271315]. The test bolus method is the most common protocol used to determine the scan timing in multi-phase CT of the canine liver and pancreas [832].…”
Section: Introductionmentioning
confidence: 99%
“…To maximize contrast enhancement of the target organ for each phase, contrast-enhanced CT techniques such as fixed scan delay, test bolus, and bolus tracking, which provide information for CT scan timing, have been described for multi-phase CT imaging in humans [1271315]. The test bolus method is the most common protocol used to determine the scan timing in multi-phase CT of the canine liver and pancreas [832].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that there was no signi cant difference in parenchymal enhancement between ABT and FTD technique in Mehnert's study [13]. Adibi et al compared liver enhancement between ABT and FTD technique and found that there was no signi cant difference in contrast enhancement of the aorta and spleen at arterial phase, but has no effect on liver enhancement [14]. As for CT scanning in children, White reported that better results was yielded by FTD trials and recommended that after CM administered, the scan to start initiate after a delay of 10-20 second.…”
Section: Discussionmentioning
confidence: 94%
“…This method is adequate for the majority of the population, but is problematic when there is abnormal anatomy, abnormal cardiac function, or severe arterial disease, all of which can significantly alter the transit time of blood. Despite known limitations, there is typically no significant difference in arterial phase enhancement with the fixed time-delay imaging technique in comparison to bolus tracking [ 7 ].…”
Section: Techniquementioning
confidence: 99%